Protective CD8+ T Cell Response Induced by Modified Vaccinia Virus Ankara Delivering Ebola Virus Nucleoprotein - Alexandra Kupke; Asisa Volz; Erik Dietzel; Astrid Freudenstein; Jörg Schmidt; Hosam Shams-Eldin; Sylvia Jany; Lucie Sauerhering; Verena Krähling; Michelle Gellhorn Serra; Christiane Herden; Markus Eickmann; et al. (Vaccines, 2022)
The urgent need for vaccines against Ebola virus (EBOV) was underscored by the large outbreak in West Africa (2014–2016). Since then, several promising vaccine candidates have been tested in pre-clinical and clinical studies. As a result, two vaccines were approved for human use in 2019/2020, of which one includes a heterologous adenovirus/Modified Vaccinia virus Ankara (MVA) prime-boost regimen. Here, we tested new vaccine candidates based on the recombinant MVA vector, encoding the EBOV nucleoprotein (MVA-EBOV-NP) or glycoprotein (MVA-EBOV-GP) for their efficacy after homologous prime-boost immunization in mice. Our aim was to investigate the role of each antigen in terms of efficacy and correlates of protection. Sera of mice vaccinated with MVA-EBOV-GP were virus-neutralizing and MVA-EBOV-NP immunization readily elicited interferon-γ-producing NP-specific CD8+ T cells. While mock-vaccinated mice succumbed to EBOV infection, all vaccinated mice survived and showed drastically decreased viral loads in sera and organs. In addition, MVA-EBOV-NP vaccinated mice became susceptible to lethal EBOV infection after depletion of CD8+ T cells prior to challenge. This study highlights the potential of MVA-based vaccines to elicit humoral immune responses as well as a strong and protective CD8+ T cell response and contributes to understanding the possible underlying mechanisms.